Biochar as Influenced by Feedstock Variability: Implications and Opportunities for Phosphorus Management - Freitas, Andressa M.; Nair, Vimala D.; Harris, Willie G. (Frontiers in Sustainable Food Systems, 2020)
Agricultural wastes from plant and animal operations are often land applied to recycle and manage residues. Compositional variability among these wastes is vast. Some waste components can potentially represent a threat to the environment and humans depending on their nature, application loads and soil type. Biochar, the product obtained by biomass heating under oxygen-limited conditions, has the potential to minimize risks associated with waste characteristics while promoting soil health. However, variation in the residue wastes (feedstocks) used to produce biochar carries over to the resultant biochar. In this study, we compare the chemistry and composition of biochars representing two broadly defined sources – animal (poultry litter, biosolids) and plant (mixed hardwoods, pure maple, pine) – and highlight phosphorus (P) management implications and opportunities presented by the variability among them. We also evaluate P leaching patterns of four selected biochars, (poultry litter, biosolids, hardwoods and maple) as applied at an identical rate (1% w/w) to two soils differing in P retention capacities. Cumulative P release following poultry litter biochar application and 20 leaching events was much lower for the more P retentive soil. Total P release from biochar-amended soils did not differ between soils when biochar from biosolids or from plant sources were used as the soil amendment. However, the biosolids-biochar released higher levels of P initially from the Candler compared with the Apopka soils, similar to that of poultry litter biochar. Compositional variations in feedstocks and resultant biochars must be understood in order to judiciously use them as crop nutrient amendments. There is potential to minimize nutrient deficiencies and environmental liabilities of biochars by matching feedstocks, or mixtures of feedstocks, to the needs of specific crops, and by considering the P retentive capacity of the soil where the biochar is applied.